Building Hierarchical Martensite - Schwabe, Stefan; Niemann, Robert; Backen, Anja; Wolf, Daniel; Damm, Christine; Walter, Tina; Seiner, Hanus; Heczko, Oleg; Nielsch, Kornelius; Fahler, Sebastian (Advanced Functional Materials, 2021)
Martensitic materials show a complex, hierarchical microstructure containing structural domains separated by various types of twin boundaries. Several concepts exist to describe this microstructure on each length scale, however, there is no comprehensive approach bridging the whole range from the nano- up to the macroscopic scale. Here, it is described for a Ni-Mn-based Heusler alloy how this hierarchical microstructure is built from scratch with just one key parameter: the tetragonal distortion of the basic building block at the atomic level. Based on this initial block, five successive levels of nested building blocks are introduced. At each level, a larger building block is formed by twinning the preceding one to minimize the relevant energy contributions locally. This naturally explains the coexistence of different types of twin boundaries. The scale-bridging approach of nested building blocks is compared with experiments in real and reciprocal space. The approach of nested building blocks is versatile as it can be applied to the broad class of functional materials exhibiting diffusionless transformations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: martensitic microstructures; shape memory alloys; twin boundaries; twins-within-twins